“[T]he fault of the man and not the poet”: Sidney’s Troubled Double Vision of Thomas More’s Utopia - Lochman, Daniel T. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2018)
In the Defence of Poesy, Philip Sidney refers puzzlingly to Thomas More and Utopia. He praises the “way” this work presents a commonwealth yet faults the man who produced it. Sidney might have followed religious writers who condemned More’s Catholicism and his use of poetic fictions rather than direct assertions of what is true. In context, though, Sidney implies that his equivocation stems from More’s inconclusive dialogue and speculative discourse: genres he deems less effective than narrative in compelling readers to act virtuously. When revising his Arcadia, Sidney tests the poetics outlined in the Defence: a lengthy dialogue is interrupted by new episodes as narrative rises above rational debate and as characters become more obviously dominated by passion, not reason. Sidney’s revisions correspond to reassessments of Utopia at the turn of the century: its wit and poetry could be admired, yet its hybrid, contemplative genres seemed less compelling than narratives whose delight invites virtuous action.